2021
DOI: 10.1186/s40659-021-00327-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteome profiling of different rat brain regions reveals the modulatory effect of prolonged maternal separation on proteins involved in cell death-related processes

Abstract: Background Early-life stress in the form of maternal separation can be associated with alterations in offspring neurodevelopment and brain functioning. Here, we aimed to investigate the potential impact of prolonged maternal separation on proteomic profiling of prefrontal cortex, hippocampus and cerebellum of juvenile and young adult rats. A special attention was devoted to proteins involved in the process of cell death and redox state maintenance. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 147 publications
1
8
0
Order By: Relevance
“…One widely used model leverages maternal separation (MS) as an analog of early caregiver deprivation during the postnatal and pre-weaning periods. MS protocols typically involve the removal and isolation of pups from dam and littermates for a designated period of time over a series of days, typically ranging from 3–4 h per day from postnatal day (P) 2 to 20 (e.g., Grassi-Oliveira et al, 2016 ; Coley et al, 2019 ; Köhler et al, 2019 ; Honeycutt et al, 2020 ; Drastichova et al, 2021 ), though some research groups only maintain separations for the first 14 days of life (e.g., Uchida et al, 2010 ; Callaghan and Richardson, 2011 ; Teissier et al, 2020 ). This ELA model is widely used as it closely models early life caregiver deprivation seen in institutionalized rearing (Kundakovic and Champagne, 2015 ), and MS in rodents also shows outcomes comparable to those in humans with a history of abuse (Teicher et al, 2006 ; Nemeroff, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…One widely used model leverages maternal separation (MS) as an analog of early caregiver deprivation during the postnatal and pre-weaning periods. MS protocols typically involve the removal and isolation of pups from dam and littermates for a designated period of time over a series of days, typically ranging from 3–4 h per day from postnatal day (P) 2 to 20 (e.g., Grassi-Oliveira et al, 2016 ; Coley et al, 2019 ; Köhler et al, 2019 ; Honeycutt et al, 2020 ; Drastichova et al, 2021 ), though some research groups only maintain separations for the first 14 days of life (e.g., Uchida et al, 2010 ; Callaghan and Richardson, 2011 ; Teissier et al, 2020 ). This ELA model is widely used as it closely models early life caregiver deprivation seen in institutionalized rearing (Kundakovic and Champagne, 2015 ), and MS in rodents also shows outcomes comparable to those in humans with a history of abuse (Teicher et al, 2006 ; Nemeroff, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored the effects of maternal separation on newborns and their mothers. Animal experiments (Alves et al, 2020; Drastichova et al, 2021; Tractenberg et al, 2016) found that maternal separation not only affected the neurodevelopment of pups by modulating the expression profiles of proteins associated with cell death pathways in the brain but also had adverse effects on their mothers' mental health. Mother‐infant separation may be a major source of stressors for both parents and their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six apoptosis-related rat proteins were grouped and graphed (Figure S17); however, they were not characterized by a clear up or down trend, which could be attributed to a complex role of different proteins in the apoptotic neuronal network−brain cortex shaping processes occurring in the early rat PND period; 6 this finding was in agreement with the finding that apoptotic cell death in the rat cortex reached the highest level at PND 1. 6 Notably, there were no statistically significant PND changes reported for these proteins in the synaptosome (mouse) 1 and the synaptosome and mitochondrial (rat) 5 fractions.…”
Section: Biological Processes and Pnd Protein Changes In The Rat Cortexmentioning
confidence: 93%
“…1−5 Biological and environmental stresses and insults sustained during this period might negatively impact brain development. 6 Therefore, to be able to better assess the impact of a chemical exposure on developing brain, it is important to gather information about the biological transformations occurring during postnatal development of the animals used in toxicoproteomic studies. Working toward this goal, we applied proteomics to investigate the protein changes occurring during the early postnatal rat cortical development.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation